ANALISIS DAMPAK MAKROEKONOMI terhadap KEUNTUNGAN pada SEKTOR PERBANKAN di BEI - Tetty Tetty Sipahutar (Akuntansi Prima, 2019)
The increasing number of banking institutions in Indonesia is accompanied by an increase in literature studies related to banking institutions. It is important to update the study related to banking developments in Indonesia. This study aims to analyze the influence of the macroeconomy that affects profitability in the banking sector. The sample used in this study is the banking sector which is listed on the Indonesia Stock Exchange (IDX) for the period 2014-2017 totaling 30 banks. The results of the regression analysis showed no significant effect between GDP and inflation on ROE and had a negative direction